FRAMING NATURE AND NATION: THE ENVIRONMENTAL CINEMA OF THE NATIONAL FILM BOARD, 1939-1974 - Clemens, Michael (My University, 2018)
This project is about the visual ways people represent the nonhuman world, and the struggles over its meaning. It is the story of how the Canadian government used the National Film Board of Canada (NFB) to manufacture and sustain a national identity that was defined by its encounters with nature, and how those definitions morphed over time. The NFB was established in 1939 by the federal government. It was to be the eyes and ears of Canada, a way for Canadians to experience the nation. As a cultural institution supported by the state, the NFB is fertile ground for an examination of state discourses about nature. In particular, I analyze NFB films as vehicles for the Canadian government’s long-running nation-building project. Between 1939 and 1974, NFB filmmakers aligned their representations of nature with the views of the government. They imagined nature as a unifying symbol of national identity and as an object to be surveyed, rationalized and exploited by government institutions. Utilitarian narratives about natural resources and wilderness management served other ideological motives too. Specifically, NFB films about nature in the postwar period privileged a high modern way of seeing the environment. This project also seeks to discern instances of ideological conflict between filmmakers and official “environmental” viewpoints, where government strategies are questioned, ridiculed or reformulated in the films themselves. Although the NFB is a product of state policy as well as an interpreter of it, it was also actively involved in producing grass-roots narratives about the environment. The NFB’s directive to “interpret Canada to Canadians” unwittingly created opportunities for independent filmmakers to share their own visions of nature that often diverged from the state. This project therefore investigates moments where filmmakers used the camera as an apparatus of reflection to challenge and subvert state modes of thinking.
Keywords: Film; Canadian cinema; Nature; Environment; NFB; Environmental History